L'harmonisation des lois cantonales d'aide sociale Une analyse des obligations internationales des droits humaines - Marlétaz, Raphaël (sui generis Verlag, 2021)
The federal constitution gives the Swiss cantons a great deal of freedom to regulate their social welfare systems. There are still great differences in this area. People living in Switzerland, depending on their place of residence, do not all have access to the same benefits and therefore do not enjoy the same protection against poverty. This phenomenon has a significant impact on the enjoyment of human rights, which are the subject of international conventions ratified by Switzerland and which must be implemented throughout the country. In this context, this book examines whether these international guarantees require a harmonization of cantonal social welfare laws. In the light of the recent global pandemic of COVID-19, which does not stop at the cantonal borders and which severely affects the precarious populations of Switzerland, this question is very topical. The author responds to this question by demonstrating, according to several legal criteria, different concrete obligations of harmonization. This approach makes it possible to move towards a global response to a problem that affects and will affect in the future many individuals of the Swiss population, regardless of where they live: poverty. This doctoral thesis was defended on September 7, 2020 at the Faculty of Law of the University of Lausanne. The jury, composed of Professor Evelyne Schmid (thesis director), Professor Pascal Mahon, Professor Kurt Pärli, Professor Véronique Boillet and Professor Vincent Martenet, admitted this thesis with magna cum laude.